Strategic interactions between tax and statutory auditors and different information regimes: Implications for tax audit efficiency - Kay Blaufus; Jens Robert Schöndube; Stefan Wielenberg (Arbeitskreis Quantitative Steuerlehre (arqus), 2020)
We examine whether tax audit regimes become more efficient if (i) there are audited financial statements and (ii) tax auditors have access to the internal statutory audit report revealing information about statutory audit adjustments. Our analysis is based on a standard tax compliance game that we extend to model the strategic interaction among a firm issuing financial and tax reports, a statutory auditor, and a tax auditor. We find that the efficiency effects of additional information depend on the strength of tax auditor incentives and the weight that firms place on book income. For high-powered tax auditor incentives, we obtain no information effect on our efficiency measures. For low-powered tax auditor incentives, we find an ambiguous effect, and for mediumpowered tax auditor incentives and firms that place a high weight on book income, tax audit efficiency increases if the tax auditor has access to additional information. In the latter case, we find that granting the tax auditor access to the internal statutory audit report increases firms' tax compliance, raises tax revenues, and decreases tax audit frequency.
Keywords: H26; M41; M42; 330; Tax compliance game; Tax audit; Statutory audit; Tax audit efficiency; Strategic auditing